KORELASI PENGUASAAN KOSAKATA BIDANG LINGKUNGAN HIDUP DAN KETERAMPILAN MENULIS TEKS EKSPLANASI SISWA KELAS XI SMK NEGERI 2 PADANG - Widia, Wina; Emidar, Emidar (Universitas Negeri Padang, 2020)
ABSTRACT The purpose of this study is to describe the following matters. First, it describes the mastery of the vocabulary in the environmental field of class XI students of SMK Negeri 2 Padang. Second, describing the explanatory writing skills of the eleventh grade students of SMK Negeri 2 Padang. Third, explaining the correlation between the mastery of environmental vocabulary and the writing skills of explanatory text for grade XI students of SMK Negeri 2 Padang. This type of research is quantitative research with descriptive methods. Based on the results of the study, the following three things can be concluded. First, the vocabulary mastery of the environmental field of class XI students of SMK Negeri 2 Padang is in good qualifications (77.85). Second, the explanatory text writing skills in class XI students of SMK Negeri 2 Padang are in good qualifications (77.93). Third, there is a significant correlation between vocabulary mastery in the field of environment and writing skills in explanatory text for class XI students of SMK Negeri 2 Padang on the degree of freedom n-1 and a significant level of 95% so that it can be concluded that H0 is rejected and H1 is accepted because the test results prove that tcount is greater ttable 4.93> 1.68. Kata Kunci: Korelasi, Kosakata Bidang Lingkungan Hidup, Menulis Teks Eksplanasi